After 12 consecutive miscarriages, a patient received immunosuppressive treatment and delivered an intact baby - Nakagawa, Koji (Reprod Med Biol, 2017)
AIM: An immune etiology for idiopathic recurrent miscarriage is an important issue because a fetus is allogenetically different from the mother. Type 1 T helper (Th1) and Type 2 (Th2) cells have important functions in immune responses and there is a general agreement that pregnancy is associated with Th2 cell dominance. The purpose of this case report is to establish the effectiveness of an immunosuppressive treatment for a patient who had 11 consecutive miscarriages despite several treatments, such as anticoagulation, that showed elevated Th1/Th2 cell ratios. METHODS: This patient visited our clinic following 11 consecutive miscarriages between 2009 and 2014 that occurred between 5 and 8 weeks’ gestation. The Th1/Th2 cell ratio was evaluated after the 12th conception and she received an immunosuppressive treatment (tacrolimus; 1 mg/d). RESULTS: The Th1/Th2 cell ratio was elevated after the 12th conception, but the patient miscarried, with a normal karyotype of chorionic villi despite the immunosuppressive treatment. After the 13th conception, she began receiving treatment with 2 mg/d of tacrolimus at 4 weeks’ gestation, which was continued until delivery. CONCLUSION: For recurrent miscarriage cases that show an elevated Th1/Th2 cell ratio after achieving pregnancy, immunosuppressive treatment with tacrolimus could be effective.